Chronic infections with viruses or parasites: breaking bad to make good. Issue 4 (19th January 2017) - Godkin, Andrew; Smith, Katherine A.
Summary: Eukaryotic forms of life have been continually invaded by microbes and larger multicellular parasites, such as helminths. Over a billion years ago bacterial endosymbionts permanently colonized eukaryotic cells leading to recognized organelles with a distinct genetic lineage, such as mitochondria and chloroplasts. Colonization of our skin and mucosal surfaces with bacterial commensals is now known to be important for host health. However, the contribution of chronic virus and parasitic infections to immune homeostasis is being increasingly questioned. Persistent infection does not necessarily equate to exhibiting a chronic illness: healthy hosts (e.g. humans) have chronic viral and parasitic infections with no evidence of disease. Indeed, there are now examples of complex interactions between these microbes and hosts that seem to confer an advantage to the host at a particular time, suggesting that the relationship has progressed along an axis from parasitic to commensal to one of a mutualistic symbiosis. This concept is explored using examples from viruses and parasites, considering how the relationships may be not only detrimental but also beneficial to the human host. Abstract : Infections can result in debilitating disease by compromising the immune system of the host. However, chronic infections have developed wily ways to avoid immune detection that can often also provide some benefit to the host. Here, we highlight and discuss examples of chronic virus and parasite infections, whose influence breaks bad and exerts good.